NEPHROPROTECTOR EFFECT OF MURAMYLDIPEPTIDE IN CADMIUM INDUCED WISTAR RATS - G. REVATHI; P. SUVARNALATHA DEVI; P. JAYALAKSHMI; N. D. PRASANNA; S. K. SHAHEEN (The Bioscan, 2010)
Cadmium is a toxic element which enters body via a number of routes including food, water, air and through cigarette smoke. The cadmium may inhibit lipogenesis by binding with the thiol group (SH) of coenzyme A. Nacetyl muramyl L-alanyl D-isoglutamine (MDP), is the minimal structural sub unit obtained from the gram positive bacteria like Mycobacterium tuberculosis. After 10th day of injection CDIR (Cadmium chloride induced rats) group showed cystic dilatation of tubules, focal inter tubular infiltration of mononuclear cells, dilatation of bowmen’s capsules and focal areas of hemorrhages. These changes were slightly aborted to normal condition after the treating with of MDP to CDIR group which were designated as MDPT. In the present study MDP showed both immunomodulating and nephroprotector effects. .